Evaluación del crecimiento de pleurotus ostreatus “Callampa” sobre cascarilla de arroz - Liñan Escate, Luis Freyder (2014)
Currently in the Moyobamba province is the rice cultivation, whose activity is the livelihood of many people, of this crop mainly originates as residual material the rice husks. Nowadays it is advisable restores residual materials to the productive cycles, which contributes to the natural resources saving, to the reduction in the residues generation and to the decrease of the environmental impact that they could generate for an inadequate disposition. To use agricultura! residues as substratum for the culture of eatable fungi is a clear example of residues valuation. In this context, it is necessary to evaluate if the rice husk can be in use as substratum for the culture of these foodstuffs (Pleurotus ostreatus), determining its parameters ofproductivity, physical properties of the substratum For it there were pro ved three rice husk proportions (97 %, 87 % and 82 %) having as witness straw of rice to 97 %. They proceeded all the treatments to inoculate with an alone variety of vine-stock The performance (EB) of the treatment 1 was very superior (14,78 %, 10,08 % and 13,22 %) to the treatments 2, 3 and 4. But they were perceived as not acceptable from the commercial point of view for which must look for a performance (Biological Efficiency) major of 50%. (Guarin and Ramirez 2004). The substratum prepared from rice husk (T2) hada performance (Biological Efficiency) referentemente it goes down (1, 32 %, 0,86% and 1,06) and for the treatments 3 and 4 adding percentages of bran of wheat the performance was slightly significant. These values are considered to be negatives for the production of Pleurotus ostreatus. In conclusion, the straw to 97% on average was significantly higher than that of rice husks to 97 %, 87 % and 82% respectively, which shows us that with the rice husk if it can be used for the production of Pleurotus ostreatus but with low yields in comparison of the straw to 97 %.